Simulasi Gerak Pengejaran Misil terhadap Target dengan Lintasan Melingkar Menggunakan Python - Lourensia Bravini Lahera; Cinta Marcella Namira; Elisa Siregar; Dewi Wulandari; Howard Situmorang; Yuni Warty (Universitas Nurul Huda, 2025)
This study aims to model the pursuit motion between guided missiles and a circularly moving aircraft using Python-based numerical simulation. The target moves along a circular path with a constant angular speed, while the missile follows a pure pursuit strategy, continuously adjusting its path toward the target's current position. Two scenarios are simulated: single pursuer and multi-agent pursuers. In the single-missile scenario, the missile forms a spiral trajectory and intercepts the target in approximately 4.9 seconds. In the multi-agent configuration, five missiles launched from different vertical positions successfully destroy the target within 8.3 seconds, with the first interception occurring at 6.7 seconds. The model is based on numerical solutions of differential equations governing relative motion dynamics. The results demonstrate that increasing the number of pursuers enhances interception speed and system effectiveness. The study is supported by animations, distance-time graphs, and damage analysis.